Utilizing the Online Shopping Market Platform: Retail Cosmetic Products - Avianti, Widiya; Adam, Duki; Hardiani, Andlisa Shiamara (Clean and Sustainable Production, 2024)
Marketing strategies are needed in retail businesses, especially cosmetic products. In-depth identification is needed to get the right strategy to increase product sales. The qualitative research method by conducting SWOT analysis is able to determine the strategy. The strategy results from identifying weaknesses that need to be minimised and taking advantage of existing opportunities. The need for additional employee personnel to manage administration and customer service online, with limited HR costs can conduct online recruitment in various online recruitment applications. Proper communication training so that online administration and customer service can handle customer complaints so that problems that occur regarding purchase transactions can be resolved immediately (zero complaints). Developed the company's website by creating creative and engaging video content to illustrate the cosmetics retail situation. Limiting the COD feature to avoid the risk of some customers not understanding the facility, but still making the online marketing programme follow the trends.